2019
DOI: 10.18203/2349-2902.isj20193341
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of various techniques of incisional hernia repair in a tertiary care center at Bikaner (North-West Rajasthan)

Abstract: Background: Incisional hernia can be defined as an internal abdominal wall defect that develops after a previously closed laparotomy. Aim of present study was to compare open suture repair and mesh repair (onlay and sublay), various factors predisposing to incisional hernia and evaluate complications following surgery for incisional hernias.Methods: A prospective study was conducted in 60 cases of incisional hernia admitted in Department of General Surgery, PBM Hospital Bikaner between October 2017 to Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In the present study, 73.3% of the cases developed incisional hernia through a midline incision. This coincides with the results of Singh et al who found that midline incision was the original incision upon which the hernia developed in 85% of the cases [10] . Ahmed and Mehboob reported that in 64.6% of their cases, incisional hernia developed on top of a midline incision [6] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, 73.3% of the cases developed incisional hernia through a midline incision. This coincides with the results of Singh et al who found that midline incision was the original incision upon which the hernia developed in 85% of the cases [10] . Ahmed and Mehboob reported that in 64.6% of their cases, incisional hernia developed on top of a midline incision [6] .…”
Section: Discussionsupporting
confidence: 91%
“…This shows a slight increase in the incidence of incisional hernia in the female gender. The higher percentage of incisional hernia in females might be due to laxity of abdominal wall muscles after multiple pregnancies and also increased incidence of obesity in females [10] . This is similar to the results obtained by Kurzer et al, in their study of the long term results of sublay mesh repair of incisional hernia in 125 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher percentage of incisional hernia in females might be due to laxity of abdominal wall muscles after multiple pregnancies and also increased incidence of obesity in females . 2 The most common risk factor for development of incisional hernia was the occurrence of wound infection after the previous surgery that was found in 46.67% of their cases. Also obesity, smoking, chronic cough, diabetes mellitus and anemia were important risk factors for incisional hernia development .…”
Section: Introductionmentioning
confidence: 99%